Aerobic Photooxidation of Toluene Derivatives into Carboxylic Acids with Bromine–Water under Catalyst-Free Conditions - Kirihara, Masayuki; Sakamoto, Yugo; Yamahara, Sho; Kitajima, Atsuhito; Kugisaki, Naoki; Kimura, Yoshikazu (Synlett, 2022)
The photoirradiation of toluene derivatives with two equivalents of bromine in benzotrifluoride–water provided a satisfactory yield of the corresponding benzoic acid derivatives. Either a fluorescent lamp, blue LED (454 nm), or UV LED (385 nm) was used for the photoreaction. The reaction pathway might proceed through the dibromination of benzylic carbon, generation of the benzylic radical via oxidative C–H abstraction, formation of benzoyl bromide, and hydrolysis of carboxylic acid.
Keywords: oxidation; toluene; benzoic acid; carboxylic acid; bromine; aerobic oxidation; photoreaction